Transformation of Islamic Religious Education in the Context of Multiculturalism at SMA Negeri 9 Yogyakarta Through an Inclusive Approach - Dwi Afriyanto; Anatansyah Ayomi Anandari (Jurnal Pendidikan Agama Islam, 2024)
Purpose – This study aims to analyze the transformation of Islamic religious education in SMA Negeri 9 Yogyakarta, including changes in curriculum, teaching methods, and social interaction, to create inclusive and responsive education towards cultural and religious diversity. Design/methods/approach – This study is qualitative research involving school principals, Islamic teachers, students, and parents of students at SMA Negeri 9 Yogyakarta as research subjects. Data were collected through participatory observation to understand school interactions and document analysis for understanding Islamic curriculum and religious materials. Findings – The research showed significant results in the transformation of Islamic religious education at SMA Negeri 9 Yogyakarta in the context of multiculturalism. The results revealed the relevant application of inclusive learning methods and Islamic religious education (PAI) materials. It comprised the integration of Quranic verses that emphasize faith and tolerance, as well as the expansion of fiqh material to include aspects of fiqh siyasah that respect ethnic, cultural, and religious diversity. Moreover, moral (akhlaq) learning was focused on understanding good behavior towards various entities, including Allah, Apostles, fellow human beings, oneself, and the environment, which contributed to the formation of the foundations of nationhood. The Islamic Cultural History (SKI) material was also adapted to provide practical examples in a multicultural context. These results confirm that schools have taken concrete steps to adjust Islamic religious education to the needs of a modern multicultural society. Research implications/limitations – Future research may conduct comparative studies in other schools, evaluate the long-term impact of multicultural approaches, examine the role of communities and parents, develop curriculum and pedagogy, and analyze the role of teachers and school collaboration strategies in supporting multicultural Islamic religious education. Originality/value – The transformation of Islamic religious education at SMA Negeri 9 Yogyakarta has succeeded in creating an inclusive and harmonious environment amidst religious diversity. This can make a positive contribution to shaping the attitude of tolerance and harmony between religious communities among students.